A Computerized Information System for a Pain Clinic - Hildebrandt, J.; Klar, R.; Weyland, A.; Wieding, J. U. (Methods of Information in Medicine, 1987)
The concept of the pain clinic constitutes a recent medical development requiring a thorough documentation of patient-related data in order to achieve reasonable standards in diagnosis and treatment, to ensure that the follow-up maintains these standards and to supply necessary data for research on the epidemiology, etiology, and therapy of chronic pain. We, therefore, developed a set of medical questionnaires for pain patients together with a microcomputer system for the storage and analysis of the data obtained. The main features of our approach are the problem-oriented medical records, the multi-user system and the immediate availability of the supplied data to every therapist using the system.
Keywords: Pain Clinic; Multi-User System; Micro-Computer; Problem-Oriented Medical Record